Journals of the Century, 1st edition - Stankus, Tony (Routledge, 2020)
This book, first published in 2002, gathers some of America's top subject expert librarians to determine the most influential journals in their respective fields. 32 contributing authors reviewed journals from over twenty countries that have successfully shaped the evolution of their individual specialties worldwide. Their choices reflect the history of each discipline or profession, taking into account rivalries between universities, professional societies, for-profit and not-for-profit publishers, and even nation-states and international ideologies, in each journal's quest for reputational dominance. Each journal was judged using criteria such as longevity of publication, foresight in carving out its niche, ability to attract & sustain professional or academic affiliations, opinion leadership or agenda-setting power, and ongoing criticality to the study or practice of their field.